The Effect of Work-Life Balance and Job Satisfaction on Self-Esteem of Civil Servants at UPT Puskesmas Sungai Ambawang in Kubu Raya Regency - Ajeng Wulandari Liyandar; Arninda Arninda (Universitas KH. Abdul Chalim Mojokerto, 2026)
The purpose of this study is to determine the effect of work-life balance and job satisfaction on the self-esteem of Civil Servants at UPT Puskesmas Sungai Ambawang, Kubu Raya Regency. The research method used is the associative method. The population in this study was all Civil Servants at UPT Puskesmas Sungai Ambawang, Kubu Raya Regency totaling 46 people (excluding the head of the puskesmas). The number of samples was 46 respondents with a total sampling technique. Data analysis techniques used multiple linear regression analysis, correlation coefficient, coefficient of determination, simultaneous influence test (F test), and partial influence test (t test). The results of multiple linear regression analysis show the equation: Y = 1.279 + 0.283X1 + 0.276X2. The correlation coefficient value is 0.740, meaning the correlation between the work-life balance and job satisfaction variables with self-esteem is strong. The coefficient of determination shows a value of 0.548, meaning 54.8% of self-esteem can be explained by work-life balance and job satisfaction, while the remaining 45.2% is influenced by other variables not included in this study. The results of the simultaneous influence test show that there is a significant simultaneous (joint) effect between work-life balance and job satisfaction on self-esteem. The results of the partial influence test show that there is a significant partial effect between work-life balance on self-esteem and there is a significant partial effect between job satisfaction on the self-esteem of Civil Servants at UPT Puskesmas Sungai Ambawang, Kubu Raya Regency.